2019
DOI: 10.1007/s12561-018-09229-9
|View full text |Cite
|
Sign up to set email alerts
|

Organizing and Analyzing the Activity Data in NHANES

Abstract: The NHANES study contains objectively measured physical activity data collected using hip-worn accelerometers from multiple cohorts. However, using the accelerometry data has proven daunting because: 1) currently, there are no agreed upon standard protocols for data storage and analysis; 2) data exhibit heterogeneous patterns of missingness due to varying degrees of adherence to weartime protocols; 3) sampling weights need to be carefully adjusted and accounted for in individual analyses; 4) there is a lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 27 publications
2
115
2
Order By: Relevance
“…Social desirability or recall bias may be present, especially for PA and SB, because of the self-reported data collection method of the NHANES. In future research, objective measures of PA and SB would help mitigate this bias (40). Original Article EPIDEMIOLOGY/GENETICS…”
Section: Discussionmentioning
confidence: 99%
“…Social desirability or recall bias may be present, especially for PA and SB, because of the self-reported data collection method of the NHANES. In future research, objective measures of PA and SB would help mitigate this bias (40). Original Article EPIDEMIOLOGY/GENETICS…”
Section: Discussionmentioning
confidence: 99%
“…As a result, reproducibility of our results in the UK Biobank is limited. In the interest of disseminating our work, we provide code for performing all of our analyses using the publicly accessible accelerometry data from the National Health and Nutrition Survey 2003-2006 [36] which has been organized in an analytic ready format through the R package rnhanesdata [7,37]. Our analysis is reproduced using the NHANES data via a supplementary markdown file to be uploaded to Github upon publication.…”
Section: Computation Software and Reproducibilitymentioning
confidence: 99%
“…Because physical activity (PA) levels are modifiable for most adults, PA is an attractive target for interventions aimed at improving the quality of life in older adults. In addition, features of PA are known to be highly correlated with prevalence of various health conditions [ 4 ] and risk of mortality [ 5 , 6 , 7 , 8 , 9 ]. Taken together, these observations suggest the power of monitoring PA in a free-living environment to both inform the epidemiology of healthy aging and facilitate safe, independent, home living for aging individuals if incorporated into, for example, a clinical monitoring program through individuals’ primary care provider.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular physical activity (PA) is associated with lower risk of a wide range of diseases, including cancer, diabetes, cardiovascular disease 1 , Alzheimer’s disease 2 , as well as mortality 3,4 . However, studies have indicated that large majority of US adults and adolescents are insufficiently active 5 , and thus PA interventions have great potential to improve public health.…”
Section: Introductionmentioning
confidence: 99%